IMPROVING THE ACCOUNTABILITY OF SMEs IN MALANG CITY: A STRATEGIC STEP TOWARDS GLOBAL COMPETITIVENESS - Pangesti, Nitami Galih; Soemarsono, Prinintha Nanda; Eriani, Izmi Dwira (Universitas Airlangga, 2025)
The low level of financial literacy among MSMEs directly impacts poor accountability practices. Without a sufficient understanding of basic accounting concepts, MSMEs struggle to record transactions systematically and accurately. Their ability to prepare comprehensive financial statements is crucial not only for meeting internal requirements but also for enhancing competitiveness on a global scale. To address the issues related to accountability practices, educational efforts on balance sheets, income statements, and the preparation of application-based financial reports are essential. The community service activity titled